2018
DOI: 10.1002/ldr.2941
|View full text |Cite
|
Sign up to set email alerts
|

An improved method for determination of aggregate stability using laser diffraction

Abstract: Soil aggregate water stability is very important from both scientific and practical points of view. This stability is a critical factor in a soil's susceptibility to water erosion and, in turn, land degradation. The most popular measure of soil aggregate stability is the water resistance index (WRI), which is commonly measured using the wet‐sieving method. Using the laser diffraction method in order to observe changes in the median of the particle size distribution and determine soil aggregate stability was fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…Therefore, it can be determined that soil properties contribute significantly to predicting MWD, specifically organic matter. This can be supported by previous studies, which showed the high correlation between OM and SAS (Abiven et al, 2009;Chaplot and Cooper, 2015) and that OM represents a significant contributor in the prediction of MWD (Bieganowski et al, 2018;Rivera and Bonilla, 2020). Also, Annabi et al (2017) reported the significant weight of clays in the pedotransfer-function of MWDfw, which confirms the current study's results on the contribution of clay in the prediction of different SAS tests.…”
Section: Determining the Relative Importance Of Variablessupporting
confidence: 91%
“…Therefore, it can be determined that soil properties contribute significantly to predicting MWD, specifically organic matter. This can be supported by previous studies, which showed the high correlation between OM and SAS (Abiven et al, 2009;Chaplot and Cooper, 2015) and that OM represents a significant contributor in the prediction of MWD (Bieganowski et al, 2018;Rivera and Bonilla, 2020). Also, Annabi et al (2017) reported the significant weight of clays in the pedotransfer-function of MWDfw, which confirms the current study's results on the contribution of clay in the prediction of different SAS tests.…”
Section: Determining the Relative Importance Of Variablessupporting
confidence: 91%
“…Aggregates are composed of mineral and organic matter that are joined by electrostatic charges, microbial muscilages, oxides, hydroxides and carbonates (Tisdall and Oades, 1982; Rengasamy et al ., 1984; Bryan, 2006). The stability of aggregates depends on the soil texture, clay mineralogy, concentration of soil organic carbon (SOC), type and concentration of cations, sesquioxide content and carbonates (Colombo and Torrent, 1991; Le Bissonnais, 1996; Amézketa, 1999; Chenu et al ., 2000; Peng et al ., 2015; Wang et al ., 2016; Maltoni et al ., 2017; Bieganowski et al ., 2018; Xue et al ., 2019). Among these properties, exchangeable sodium percentage (ESP), Fe and Al oxides and hydroxides, and SOC seem to play a major role in aggregate stability, with a debate as to which of them are more effective (Le Bissonnais, 1996; Six et al ., 2004; Xue et al ., 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Since the last century, sedimentation-type PSD methods have been used to measure the stability of these microaggregates (Kachinsky 1965;Abu-Sharar-Bingham-Rhoades 1987). More recently, the laser diffraction measurement technique has been proposed to characterize the structural state of micro-aggregates, since LDM PSD measurements are significantly faster, require less sample amount and give a complete grain size distribution, than sedimentation techniques (Levy et al 1993;Bieganowski-Ryżak-Witkowska-Walczak 2010;Bieganowski et al 2018b). Various indicators are known to characterise the stability of microaggregates.…”
Section: Introductionmentioning
confidence: 99%